Water‐soluble π‐conjugated polyfluorene bearing 6‐N1‐hexylcytosine and 6‐trimethylammoniumhexyl side chains: Synthesis, chemical properties, and sensing ability for nucleoside and telomere DNA. Issue 4 (12th October 2022) - Yamaguchi, Isao; Ooe, Ryoga; Wang, Aohan
Abstract: Water‐soluble π‐conjugated polyfluorene bearing 6‐ N 1 ‐cytosinehexyl and 6‐trimethylammoniumhexyl bromide side chains, namely polymer‐1, was synthesized by Suzuki polycondensation. The absorption onset wavelength (λonset ) of the polymer was longer than that of the monomer and confirmed the presence of the π‐conjugated system along the polymer chain. The cyclic voltammetry and UV–vis analyses showed that the highest occupied molecular orbital and lowest unoccupied molecular orbital energy levels of the polymer were −5.5 and −2.6 eV, respectively. The photoluminescence (PL) intensity of the polymer decreased with increasing DNA chain length ( m ) upon adding (TTAGGG) m (T = thymine, A = adenine, and G = guanine; m  = 2, 4, 6, and 8), indicating that the polymer could detect telomere DNA chain lengths with higher precision than previously reported DNA sensors. Similarly, the PL intensity decreased with the addition of nucleosides. Photoinduced charge transfer in the complex between the polymer and DNA or nucleoside played an important role in the PL response of the polymer toward analytes. The sensing behavior was analyzed using the Stern–Volmer and Benesi–Hildebrand methods. Abstract : Water‐soluble ‐conjugated polyfluorene bearing 6‐N1‐hexylcytosine and 6‐ trimethylammoniumhexyl bromide side chains was synthesized. The polymer could detect the chain lengths of telomere DNAs, (TTAGGG)m (m = 2, 4, 6, and 8), by monitoring the decrease in the PL intensity upon the addition of DNA. The detection was completed within several minutes and without amplification of polymerase chain reaction.